Forest dynamics of a sub-xerophilous vegetation formation in central Peru - Chanchamayo Valley, Peru - Palacios-Ramos, S (2018)
Studies about the complex processes of forest dynamics in pre-montane and montane forests (between 600 - 3000 m altitude) are rare. This study contributes to our knowledge on changes in the floristic composition and population dynamics of woody species in a sub-xerophilous formation immersed in the humid pre-montane and montane forests of Peru. In 2015 we re-measured trees with diameter at breast height equal or greater than10cm in a permanent plot established in 2009. We recorded 31 species of 25 families, with a Fisher's Alpha diversity index of 7.5. The most abundant and dominant species (including Heteropterys intermedia, Physocalymma scaberrimum, Sapium glandulosum, Tachigali peruviana and Machaerium hirtum) represented 66.25% of all species in 2009 and 66.36% in 2015. The prevalence of these species and others ensures the maintenance of a characteristic seasonally dry forest formation within the census period (6.25 years). The dynamics of this forest, with a high rate of recruitment (3.82%) and a low rate of mortality (0.72%), show favorable conditions for the maintenance of this forest fragment.